2005
DOI: 10.1177/1534734605277312
|View full text |Cite
|
Sign up to set email alerts
|

Foot Infections

Abstract: Infections of the foot are very variable, some being complex in nature, causing pain, morbidity, and even mortality. In patients with diabetes mellitus, foot infections are common, ranging from chronic bacterial or fungal infections to serious limb-threatening ones. To manage infections, a sound knowledge of anatomy is essential. This article reviews the problems with respect to recent evidence and provides pathways to management and suggestions of changes with potential to wound healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…Birinci kuşak sefalosporinler (sefaleksin, sefadroksil) ve klindamisin, stafilokok ve streptokoklara karşı iyi etki gösterirler. Şiddetli selüliti olan ve hospitalizasyon gereken hastalarda, parenteral birinci kuşak sefalosporin (sefazolin sodyum gibi) tercih edilebilen antibiyotiklerdendir [16,18].…”
Section: Antibiyoterapiunclassified
“…Birinci kuşak sefalosporinler (sefaleksin, sefadroksil) ve klindamisin, stafilokok ve streptokoklara karşı iyi etki gösterirler. Şiddetli selüliti olan ve hospitalizasyon gereken hastalarda, parenteral birinci kuşak sefalosporin (sefazolin sodyum gibi) tercih edilebilen antibiyotiklerdendir [16,18].…”
Section: Antibiyoterapiunclassified
“…A systematic review of hyperbaric oxygen use in the treatment of chronic wounds found that hyperbaric oxygen can reduce the risk of amputation [31]. HBOT appears to aid in the reduction of bacterial burden by inhibiting anaerobic bacterial growth as well as enhancing antimicrobial properties of leukocytes [32]. These mechanisms would seem apropos in the treatment of DFUs because anaerobic bacteria as well as malfunctioning leukocytes both contribute to the chronicity of these wounds.…”
Section: Reducing the Bacterial Burden In Dfusmentioning
confidence: 99%
“…The lower extremity's thin soft tissue envelope is occasionally further compromised by poor vascularity from highenergy trauma, diabetes mellitus, smoking, and peripheral vascular disease. [1][2][3] Standard treatment includes aggressive operative debridement with local and systemic antibiotic administration to control infection. 2,[4][5][6][7] Such debridement can be technically demanding, 7 but the removal of all nonviable tissue is essential to creating a healthy tissue bed and decreasing the infectious load.…”
mentioning
confidence: 99%